2022
DOI: 10.1021/acs.biomac.2c00694
|View full text |Cite
|
Sign up to set email alerts
|

Smart Protein Refolding System Based on UCST-Type Ureido Polymers

Abstract: We have reported that ureido polymers exhibit upper critical solution temperature (UCST)-type phase behavior in solution, which is the opposite of lower critical solution temperature (LCST)-type behavior. Furthermore, UCST-type ureido polymers undergo liquid−liquid phase separation (LLPS) upon cooling rather than the liquid−solid phase transition of the typical LCST-type polymers. In this study, ureido polymers with hydrophobic groups were prepared to evaluate the effects of cooling-induced LLPS of UCST-type p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We have reported that ureido polymers such as poly­(allylurea), poly­(vinylurea), and poly­(2-ureidoethyl methacrylate) form liquid droplets under physiological salt and pH conditions. The droplets dissolve above the phase separation temperature ( T p ), and cooling below T p results in liquid droplets.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that ureido polymers such as poly­(allylurea), poly­(vinylurea), and poly­(2-ureidoethyl methacrylate) form liquid droplets under physiological salt and pH conditions. The droplets dissolve above the phase separation temperature ( T p ), and cooling below T p results in liquid droplets.…”
Section: Introductionmentioning
confidence: 99%
“…10 Practical applications using the complex coacervate require strategies such as chemical crosslinking to stabilize the coacervate. 11 We previously reported that ureido polymers such as polyallylurea, [12][13][14] polyvinylurea, 15,16 and poly(2-ureidoethylmethacrylate) 17,18 exhibit LLPS over wide ranges of pH and salt concentrations including in physiologically relevant conditions. As the ureido polymers form simple coacervates, we reasoned that these coacervates would be useful in biological media.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LLPS properties of the ureido polymers are thermosensitive. [12][13][14][15][16][17][18] The coacervate droplets formed by ureido polymers dissolve upon heating, and the coacervates form again when cooled below the phase separation temperature (T p ); T p is dependent on molecular weight and ureido content. Due to this unique upper critical solution temperature (UCST)-type thermoresponsive, ureido polymers can capture proteins in coacervates upon cooling 13 and can induce a switch between monolayer and spheroid cell culture upon a change in temperature.…”
Section: Introductionmentioning
confidence: 99%